Corrigendum: Ethnopharmacological Approaches for Therapy of Jaundice: Part II. Highly Used Plant Species from Acanthaceae, Euphorbiaceae, Asteraceae, Combretaceae, and Fabaceae Families - Devesh, Tewari; Andrei, Mocan; Emil D., Parvanov; Archana N., Sah; Nabavi, Seyed M.; Lukasz, Huminiecki; Zheng, Feei Ma; Yeong, Yeh Lee; Jarosław O., Horbańczuk; Atanas G., Atanasov (Frontiers Media, 2017)
In the original article, there was a mistake in the legend for Figure 4 as published (the spelling of isosilibin was incorrect). The correct legend appears below. In the original article, there was a mistake in Figure 4 as published (CH3 group was missing in the Silybin structure). The corrected Figure 4 appears below. The authors apologize for these errors and state that this does not change the scientific conclusions of the article in any way.